2008
DOI: 10.1007/s11418-007-0221-0
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 inhibitory effects and composition of the volatile oil from the dried roots of Lithospermum erythrorhizon

Abstract: The composition of the volatile oil from Lithospermi Radix, the dried roots of Lithospermum erythrorhizon (Boraginaceae), has been investigated by capillary GC and GC-MS. To investigate the anti-inflammatory activity of the oil, in-vitro inhibition of ovine cyclooxygenase-1 and 2 (COX-1 and COX-2) activity by the oil was studied. Fifty-four components of the oil were identified, representing 92.74% of the oil. The main components were 2-methylbutanoic acid (21.50%), 3-methylbutanoic acid (12.61%), 2-methylprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Apart from naphthoquinone pigments, linoleic acid [ 17 ] and β-sitosterol [ 18 ] have been identified in both in vitro cultures. Additionally, methyl linolate [ 17 ] has been isolated from the cell suspension culture (also detected by GC-MS in the roots of other Boraginaceous species [ 19 , 20 ]) as well as methyl jasmonate ( 10 ) [ 21 , 22 ] (for the first time within the Boraginaceae family), a triglyceride mixture of palmitic, stearic and 8- Ζ - or 9- Ζ - or 11- Ζ or 9- Ε -octadecenoic acid (as determined after transesterification/methylation and GC-MS analysis of the resulting fatty acid methyl esters [ 23 ]) and also a mixture of 1-monoglycerides of palmitic, stearic and oleic acid (as determined after transesterification/methylation and GC-MS analysis of the resulting fatty acid methyl esters [ 23 ], as well as after GC-MS analysis of the silylated derivatives which were identified as 2,3- O -bis(trimethylsilyl)-1-glyceryl palmitate, stearate and oleate respectively) probably for the first time within Boraginaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from naphthoquinone pigments, linoleic acid [ 17 ] and β-sitosterol [ 18 ] have been identified in both in vitro cultures. Additionally, methyl linolate [ 17 ] has been isolated from the cell suspension culture (also detected by GC-MS in the roots of other Boraginaceous species [ 19 , 20 ]) as well as methyl jasmonate ( 10 ) [ 21 , 22 ] (for the first time within the Boraginaceae family), a triglyceride mixture of palmitic, stearic and 8- Ζ - or 9- Ζ - or 11- Ζ or 9- Ε -octadecenoic acid (as determined after transesterification/methylation and GC-MS analysis of the resulting fatty acid methyl esters [ 23 ]) and also a mixture of 1-monoglycerides of palmitic, stearic and oleic acid (as determined after transesterification/methylation and GC-MS analysis of the resulting fatty acid methyl esters [ 23 ], as well as after GC-MS analysis of the silylated derivatives which were identified as 2,3- O -bis(trimethylsilyl)-1-glyceryl palmitate, stearate and oleate respectively) probably for the first time within Boraginaceae family.…”
Section: Resultsmentioning
confidence: 99%
“…owing to a wide range of various biological effects, aromatherapy may be a favourable alternative in the prevention and treatment of infections. Essential oils and their terpene components are proved to have antibacterial, antiviral, antifungal, antiparasitic, and anti-inflammatory effects [40,[48][49][50]. despite the fact that numerous studies confirm the bactericidal impact of essential oils, they still remain in the shadow of pharmacological treatments and have only an adjunctive role.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the FD-factors, it was found that β-caryophyllene oxide 60; FD-factor 128, spicy was the most intense (Tronto, Canada); Other, reference mass spectrum and retention index were measured outside the author' s laboratory (the identification is therefore considered to be tentative). e Our previous studies: 21 from miyazawa et al 14) ; 45, 47 from miyazawa et al 15) ; 56 from miyazawa et al 16) ; 63, 64, 73, 77 and 85 from miyazawa et al 17,18) ; 66 from miyazawa et al 19)…”
Section: Gc-o Aeda and Rfamentioning
confidence: 95%
“…In contrast, ageratochromene, h e x a h y d r o f a r n e s y l a c e t o n e , β -e u d e s m o l , a n d β-caryophyllene oxide were identified for the first time in this study as the components of the volatile oil from the aerial parts of P. odorata. Hexahydrofarnesyl acetone is a component of volatile oils found in many plants of families such as Fabaceae 19 , Rosaceae 25 , and Asteraceae 26 . In addition, muurolane 68; 0.90 is an unusual sesquiterpene and was identified as a characteristic compound in Malvaceae for the first time.…”
Section: Constituents Of Volatile Oil From Pavonia Odoratamentioning
confidence: 99%